2006
DOI: 10.1002/pssb.200565230
|View full text |Cite
|
Sign up to set email alerts
|

Doping of GaN with Fe and Mg for spintronics applications

Abstract: Metal-organic chemical vapour deposition of GaN : Fe and (Ga, Fe)N : Mg has been carried out in order to optimize the growth process and to investigate the effectiveness of Fe ions and Mg acceptors incorporation. All samples have been investigated via high-resolution X-ray diffraction, secondary-ion mass spectroscopy, electron paramagnetic resonance (EPR) and magnetization measurements. Co-doping of Fe and δ -Mg has been found to promote the acceptors incorporation and EPR data, supported by superconducting qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
(14 reference statements)
1
10
0
2
Order By: Relevance
“…17 The metalorganic chemical vapor deposition (MOCVD) of GaN:Fe has been previously reported, with a focus on the actual Fe content in the layers and its effect onto the carrier concentration. 18 More recent preliminary works by others 19 and us 20,21 indicate that MOCVD grown (Ga,Fe)N shows ferromagnetic-like characteristics to above room temperature. Moreover, diluted magnetic semiconductors, and (Ga,Fe)N in particular, have become model systems to test various implementations of the density functional theory to disordered strongly correlated systems.…”
Section: Introductionmentioning
confidence: 94%
“…17 The metalorganic chemical vapor deposition (MOCVD) of GaN:Fe has been previously reported, with a focus on the actual Fe content in the layers and its effect onto the carrier concentration. 18 More recent preliminary works by others 19 and us 20,21 indicate that MOCVD grown (Ga,Fe)N shows ferromagnetic-like characteristics to above room temperature. Moreover, diluted magnetic semiconductors, and (Ga,Fe)N in particular, have become model systems to test various implementations of the density functional theory to disordered strongly correlated systems.…”
Section: Introductionmentioning
confidence: 94%
“…In order to investigate the potential of Fe-doped GaN as DMS for future spintronic applications, (Ga,Fe)N layers have been recently fabricated by various techniques such as ion implantation [2,3], molecular beam epitaxy (MBE) [4,5], metal-organic vapor phase epitaxy (MOVPE) [6,7], and hydride vapor phase epitaxy (HVPE) [8]. Both low temperature [4] and RT [3] ferromagnetisms have been reported for this materials system and the controversial findings suggest the magnetic behavior as being influenced by the employed growth technique and by the deposition parameters.…”
Section: Introductionmentioning
confidence: 99%
“…This effect can be attributed to a periodic Mg profile within the crystal [5]. Moreover, a separation of multiple dopants can be achieved yielding higher doping efficiencies as demonstrated recently [8]. However, few studies on the d-doping techniques during the deposition of GaN have been reported [6], giving still potential for further growth-and structural-studies.…”
Section: D-dopingmentioning
confidence: 92%